Participatory on - Farm Evaluation and Demonstration of Improved Herbaceous Forage Species in Irrigated Lowlands of Dassench Woreda of South Omo Zone (Global Journal of Science Frontier Research, 2017)
Participatory on farm improved forage species evaluation was conducted at Keelewe Peasant association of Dassench Woreda of South Omo Zone in the 2014 under irrigated condition using the improved forage legumes to identify the adaptable and high biomass yielding forage species. The field experiment was laid out in a Randomized Complete Block Design (RCBD) with four replications per tested species. The improved forage legume species tested in this study were Lablab purpureus, Lablab intoritum and Vigna unguiculatium. The dry matter yield obtained in this study revealed that there was none significance difference (p > 0.05) among the tested improved forage legume species in the study area. The dry matter yield production potential of tested species under irrigated condition in to the study area is 15.91, 14.16 and 15.40 t/ha for Lablab intoritum, Lablab purpureus and Vagigna ungulatium respectively.
Keywords: dry matter yield; lablab intoritum; lablab purpureus; vigna unguiculatium